Analysis of Urban Morphology and Microclimate in Nigeria: Case Study of Three Cities (Port Harcourt, Lagos and Jos) - Alexander Chinago Budnukaeku; Frank Bikume Mokie S.; Ajiboye Samson A. (Innovation in Science and Technology, 2025)
This study investigates the relationship between urban morphology and microclimate in three Nigerian cities: Port Harcourt, Lagos, and Jos. The research aims to understand how different urban forms and structures impact local climatic conditions, such as temperature, humidity, and wind patterns, and how these variations affect residents’ thermal comfort. The methodology combines historical data analysis with primary data collected through a structured questionnaire distributed to residents in each city. A Likert scale was used to gauge perceptions of microclimate, and the data were analyzed using simple statistics and correlation analysis to identify significant patterns and relationships. The results indicate that urban morphology plays a crucial role in shaping the microclimate of each city. High-density urban areas, particularly in Lagos and Port Harcourt, are associated with higher temperatures and increased occurrences of extreme heat. These findings are consistent with the urban heat island effect, where densely built environments trap heat, exacerbating temperature rises. Conversely, Jos, with its higher altitude and more dispersed urban form, experiences more moderate temperatures and better ventilation, contributing to more favorable microclimatic conditions. Statistical analyses reveal significant correlations between building density and extreme heat experiences, underscoring the importance of urban planning in mitigating adverse microclimatic effects. The presence of green spaces emerged as a critical factor in moderating local climate, with areas featuring more greenery reporting lower temperatures and higher levels of thermal comfort among residents. This highlights the role of urban greening in enhancing livability and resilience to climate change. The study’s findings emphasize the need for sustainable urban planning practices that incorporate green infrastructure and consider the local climatic impacts of urban form. Recommendations include increasing green spaces, implementing climate-responsive building designs, and enhancing public awareness of sustainable living practices. By adopting these strategies, urban planners can improve microclimatic conditions and overall urban livability in Nigerian cities. In conclusion, this research provides valuable insights into the complex interactions between urban morphology and microclimate. It underscores the need for integrated planning approaches that prioritize environmental sustainability and human comfort, ultimately contributing to the development of healthier and more resilient urban environments.